2016
DOI: 10.4038/sljog.v37i4.7773
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and practices regarding antenatal exercises among pregnant mothers attending De Soyza Maternity Hospital Colombo

Abstract: Introduction: Antenatal exercises provide many health benefits not only to pregnant mothers but also to the fetuses. Adequate knowledge among pregnant mothers is vital to promote practicing of it. The aim of this study was to describe the knowledge, attitudes and practices regarding antenatal exercises and factors associated with them among pregnant women attending De Soyza Maternity Hospital (DMH) Colombo. Methods:A descriptive cross-sectional study was conducted among 110 pregnant mothers with a period of am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
17
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 4 publications
6
17
2
Order By: Relevance
“…These results are consistent with a study conducted by Khatri et al (2014), mentioned that most of the study sample they can attend an antenatal education program once weekly for half an hour [22]. Regarding the association between the age of pregnant women and overall knowledge related to exercise during pregnancy was not statistically significant, these results are consistent with findings of other studies, which showed that no statistically significant association between age of pregnant women's and overall knowledge [15,16,17]. There was a significant relationship between the level of education and pregnant women's overall exercises knowledge during pregnancy this results is agree with the findings of Loveness et al (in 2014), which reported that were significant associations between adequate knowledge of physical exercise during pregnancy and their education level [21] and also is in agreement with study conducted by Atiya & Muhammad in 2014 , who showed that level of knowledge about exercise increase with increasing level of education [22]…”
Section: Acrosssupporting
confidence: 85%
See 2 more Smart Citations
“…These results are consistent with a study conducted by Khatri et al (2014), mentioned that most of the study sample they can attend an antenatal education program once weekly for half an hour [22]. Regarding the association between the age of pregnant women and overall knowledge related to exercise during pregnancy was not statistically significant, these results are consistent with findings of other studies, which showed that no statistically significant association between age of pregnant women's and overall knowledge [15,16,17]. There was a significant relationship between the level of education and pregnant women's overall exercises knowledge during pregnancy this results is agree with the findings of Loveness et al (in 2014), which reported that were significant associations between adequate knowledge of physical exercise during pregnancy and their education level [21] and also is in agreement with study conducted by Atiya & Muhammad in 2014 , who showed that level of knowledge about exercise increase with increasing level of education [22]…”
Section: Acrosssupporting
confidence: 85%
“…(3) Muhammad (2014) reported that 81.2% of the study sample had inadequate knowledge regarding the effect of exercise during pregnancy [17] and Wijesiriwardana & Gunawardena (2015) showed the majority of their study sample had poor knowledge concerning antenatal exercise [16]. pregnant women that involved in this study had poor knowledge about types of antenatal exercises such as walking, leg raising, pelvic floor, and yoga, these results are inconsistent with a study carried out by Chidozie et al (2014), reported that most of the women had knowledge of pelvic floor exercise, muscle strengthening exercise, and relaxation and breathing exercise as types of antenatal exercises [19].…”
Section: Acrossmentioning
confidence: 99%
See 1 more Smart Citation
“…Though, surveys have exhibited that majority of pregnant females engage less in regularly exercise [18] and that less than 20% accept upto-date exercise recommendations [19]. Several authors have explored the attitude and approaches of females regarding the routine of bodily activity during pregnancy as well as the causes that influence their conduct concerning exercise [20][21]. Therefore, the current study was performed to appraise the awareness and attitude about exercise during pregnancy among antenatal mothers…”
Section: Inmentioning
confidence: 98%
“…However, the appropriate knowledge and attitude regarding kegel exercises during the postpartum period among mothers, have been shown to be vital in improving the practice, as well as an insight into appropriate attitude, in the context of socio-cultural, educational and economic background of the mothers is essential in providing an educational intervention to promote adherence to Kegel exercises (Wijesiriwardana &Gunawardena, 2016).Moreover, recognizing the factors that affect behaviours and beliefs would enhance a change in attitude. Therefore, identifying the knowledge and attitude about exercise among women may help to determine the women adherence to kegel exercise during pre and postnatal period (Mbada, 2014).…”
Section: Introductionmentioning
confidence: 99%